Association of intratumoral microbiome diversity with hepatocellular carcinoma prognosis - Fengle Jiang; Yuan Dang; Zheting Zhang; Yanan Yan; Yingchao Wang; Yi Chen; Lihong Chen; Jialiang Zhang; Jingfeng Liu; Jianmin Wang (mSystems)
ABSTRACT The evidence that intratumoral microbiomes, as a rising hallmark of cancer, have a profound impact on cancer phenotypes is increasingly compelling. However, the impact of the composition and diversity of the intratumoral microbiome on the prognosis of patients undergoing surgical resection for hepatocellular carcinoma (HCC) remains incompletely understood. In this study, we revealed a high abundance of bacteria in the neoplastic tissues. The presence of bacterial lipopolysaccharide and lipoteichoic acid was detected alongside tumor-associated immune cells. By utilizing 16S rRNA gene sequencing, we identified a specific intratumoral microbiome signature that was highly predictive of the prognosis for HCC patients who underwent surgical resection. Specifically, the presence of Intestinimonas, Brachybacterium, and Rothia were identified as independent risk factors for the overall survival of HCC patients who underwent surgical resection.IMPORTANCEAlthough some studies have shown an abundance of bacteria in hepatocellular carcinoma (HCC), there is still limited understanding of the composition and diversity of the intratumoral microbiome that is favorable or adverse to the prognosis of HCC patients. Our results indicated that a greater abundance of bacteria could be observed in the neoplastic tissues than in nonneoplastic tissues. Bacterial cell wall components largely coincided with tumor-associated immune cells. The bacteria in the long overall survival (LOS) group were associated with metabolism and cytokine‒cytokine receptor interaction pathways, while bacteria in the short overall survival (SOS) group were associated with proinflammatory and cell proliferation pathways. Notably, specific taxa could independently predict HCC prognosis. Based on these findings, intratumoral microbiomes facilitate the use of precision medicine in clinical practice.